1996
DOI: 10.1093/ndt/11.supp2.24
|View full text |Cite
|
Sign up to set email alerts
|

Vena cava diameter measurement for estimation of dry weight in haemodialysis patients

Abstract: A correct estimation of volume status and so-called dry weight in dialysis patients remains a difficult clinical problem. Clinical status and chest X-ray are not sensitive enough, while invasively measured central venous pressures are not routinely available. Recently, the sonographic determination of the diameter and collapse of the inferior vena cava (IVC) has been proposed as a noninvasive method for estimating intravascular volume. We tried to evaluate the clinical relevance of this method in dialysis pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
6

Year Published

1998
1998
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 4 publications
0
69
0
6
Order By: Relevance
“…Chang/Chen/Chen/Cheng/Chung/Yang Meanwhile, the DW for the control group patients was monitored using traditional methods. Many works have demonstrated that estimating IVCD by echocardiography offers a simple, non-invasive and reliable tool for DW determination, and correlates well with other methods such as multifrequency bioimpedance and plasma volume detected by radioiodinated serum albumin method for estimating fluid volume for chronic hemodialysis patients [10,12,23]. Besides, an experienced echocardiographic operator at the bedside can obtain this measurement more quickly and easily.…”
Section: Discussionmentioning
confidence: 92%
“…Chang/Chen/Chen/Cheng/Chung/Yang Meanwhile, the DW for the control group patients was monitored using traditional methods. Many works have demonstrated that estimating IVCD by echocardiography offers a simple, non-invasive and reliable tool for DW determination, and correlates well with other methods such as multifrequency bioimpedance and plasma volume detected by radioiodinated serum albumin method for estimating fluid volume for chronic hemodialysis patients [10,12,23]. Besides, an experienced echocardiographic operator at the bedside can obtain this measurement more quickly and easily.…”
Section: Discussionmentioning
confidence: 92%
“…As such, the usage of these biomarkers is restricted, but echocardiography and the inferior vena cava collapsibility index (IVCCI) and inferior vena cava index (IVCI) are commonly used to determine intravascular volume, especially for hemodialysis patients (8)(9)(10). It is difficult to perform these techniques with pediatric patients as these measures often vary depending on the individual performing the test, and sometimes these tests do not accurately indicate the severity of the volume loss, which greatly reduces the utility of these methods (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, one would expect that phasic changes in transmural pressure would more readily translate into respiratory variations in cross-sectional size when imposed on a partially empty vessel (hypovolemia), as opposed to a fully repleted one (normo or hypervolemia). Based on this rationale, the phasic changes in caval diameters, as evaluated from echocardiography, have been proposed as non-invasive indices of intravascular volume status [44][45][46][47][48][49][50].…”
Section: Respiratory Fluctuations Of Great Veins Geometrymentioning
confidence: 99%
“…The latter, however, only causes the IVC diameter to shrink if the vessel is not fully repleted (i.e., if it operates on the steep part rather than the plateau of its transmural pressure/ diameter relationship). Quantified in various ways with transthoracic echocardiography, the inspiratory decrease of IVC diameter has been used to characterize volume status in the course of hemodialysis for end-stage renal disease [45,46]. In the ICU, we are aware of no similar application in spontaneously breathing subjects.…”
Section: Respiratory Fluctuations Of Great Veins Geometrymentioning
confidence: 99%